Ryzodeg (Insulin Degludec/Aspart) for Type 2 Diabetes in Pakistan: A 12-Week Study on Glycemic Control and Safety Outcomes - Muhammad Murtaza Shafqat, Ali Raza Naqvi, Amir Shafique, Rashid Ali Khosa, Shabeer Ahmed, Hazar Khan Bugti (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Insulin degludec/aspart (IDegAsp), marketed as Ryzodeg, is a fixed-dose combination insulin containing insulin degludec (a long-acting basal insulin) and insulin aspart (a rapid-acting prandial insulin). This combination provides both basal and prandial insulin coverage in a single injection, offering a potential improvement in glycemic control in patients with Type 2 Diabetes Mellitus (T2DM). Objective: To evaluate the efficacy and safety of IDegAsp in a cohort of 205 patients with T2DM in Pakistan over a 12-week period. Methods: This multicenter, open-label, prospective study involved 205 patients aged 40–70 years, who were treated with IDegAsp once or twice daily. The primary endpoints included changes in HbA1c, fasting plasma glucose (FPG), and postprandial plasma glucose (PPG). Secondary endpoints included weight change, incidence of hypoglycemic events, and treatment adherence. Results: After 12 weeks, significant improvements were observed in HbA1c (mean reduction of 1.5%), FPG (mean reduction of 50 mg/dL), and PPG (mean reduction of 70 mg/dL). The mean weight reduction was 1.5 kg. Hypoglycemic episodes occurred in 15% of patients, with no severe hypoglycemia. Treatment adherence was high (90%). Conclusion: IDegAsp effectively improved glycemic control in Pakistani patients with T2DM, demonstrating a favorable safety profile with a low incidence of hypoglycemia. These results support its use as a viable therapeutic option for managing T2DM in Pakistan. Keywords: Insulin degludec/aspart, Ryzodeg, Type 2 Diabetes Mellitus, Pakistan, HbA1c, hypoglycemia, real-world study